A imprescindibilidade dos critérios linguístico-textuais na produção de documentos com força probatória e a garantia do devido processo legal - Petreca, Olívia do Carmo (Language and Law / Linguagem e Direito, 2019)
Evidence, along with a persuasive address, is presented to the judge to support a petition, in the hope of securing a favourable judgment. In tax proceedings, in both administrative and judicial courts, the evidence is predominantly documentary and produced either by the taxpayers or by the public administrators, by means of documents such as tax infraction notices, overdue liability certificates, licenses etcetera. However, for these documents to be valid, some prescriptive rules must be followed. This article presents an analysis of such documents produced by public officials and to do so uses "logical-semantic Constructivism"derived from studies produced by Paulo de Barros Carvalho. These analyses show the importance of linguistic criteria for interpreting legal texts in the area of taxation and for helping to reduce subjectivity in litigation. This article analyses cases judged by the Brazilian Supreme Court to show the exibilisation of due process when the law is applied to distortions and linguistic problems in legal texts which result in the relaxation of due process.